Syntactic Complexity in EFL and Native Learners' Undergraduate Thesis Abstracts - Murniati Murniati (Journal of English Language and Culture, 2018)
This research aims to find syntactic complexity of the abstracts in the undergraduate thesis written down by university learners in Indonesia and the ones written down by native speakers of English. The characteristics of syntactic complexity produced by Indonesian learners and the learners who are the native speakers should also be analyzed. It is possible to extend the type of syntactic complexity found in academic texts. In the end, those extensions should be characterized the English language used by Indonesian learners. The data is gained through downloading the abstracts of the undergraduate thesis in the academic year of 2015-2016 from the UBM English Department alumni database. The data regarding the abstracts written down by the native speakers is downloaded from the reputable universities in The United States of America. After that, the data is analyzed by making used of the syntactic analyzer by Lu & Ai (2015). The results shows that the Indonesian learners tend to write more complex sentences and use subordination in the abstracts. The native speakers, on the other hands, tend to write longer sentences with longer T-Unit and clauses. They also tend to write complex nominal in the abstracts. The number of coordination used is similar between the ones written down by Indonesian learners and native speakers of English. Keywords: syntactic complexity, syntactic structures, undergraduate thesis, Indonesian learners